Modelos e análises de gestão dos recursos hídricos no Brasil, nos Estados Unidos e na França - Alves, Jucicléa Santos (2024)
Although the Earth has a wide water coverage, only a small portion is available and in adequate conditions for the conservation of life and to promote economic and social development. The increase in freshwater consumption, driven by population growth, economic development and changes in consumption patterns, has caused degradation and pollution of water resources on a global scale. These problems are aggravated by the lack of sanitation and the release of domestic, industrial and agricultural effluents, reducing both the quality and quantity of water available for predominant uses. Since the 1970s, there has been a significant increase in mobilization regarding the need to manage natural resources, especially water. The Integrated Water Resources Management (IWRM) approach has gained prominence, seeking to coordinate the development of water, land and related resources to maximize economic and social well-being without harming ecosystems. Countries have adopted varied water resources management models, shaped by public policies and local administrative structures. France has implemented principles related to river basin management since 1964, through Law No. 64- 1245, with the creation of basin institutions throughout its territory. The United States adopted watershed management in the 1980s, based on the Clean Water Act (CWA). Brazil, with France as a reference, established the Water Law in 1997, adopting the integrated, decentralized and participatory management of water resources. The United States differs from Brazil and France in its management based on command and control instruments. In view of the above, the objective of this work is to develop a comparative analysis of water resources management, highlighting the differences and similarities of the models adopted, with the purpose of proposing suggestions for improving Brazilian water resources management. For this, bibliographical research was used, for theoretical foundation and knowledge of existing contributions, and documentary research, for evolutionary knowledge of the legal framework and for comparison and analysis. This, as well as other scientific studies that address this topic, is justified by the search for the evolution of methodologies, based on the sharing of experiences that improved policies related to water, considering the diversity of management models adopted. Actions were proposed to improve Brazilian management, based on the management of water resources in the United States and France. The complexity of water resources management, given the environmental and social challenges faced globally, highlights the importance of complying with water resources policies quickly and effectively to guarantee the availability and quality of water for multiple uses.